HUBUNGAN KECERDASAN EMOSIONAL TERHADAP PRESTASI BELAJAR PADA SISWA SMP NEGERI 1 PETERONGAN KABUPATEN JOMBANG - Engelberta Ronny, Maria; Prawito, Prawito; Vidhiastutik, Yusiana (PRIMA WIYATA HEALTH, 2023)
Emotional intelligence is one of the most important factors in the learning process to be able to achieve maximum achievement in classroom learning. Middle school-age children are those aged 13-15 years who are in the adolescent developmental age group in the early phases of psychological development. The research objective was to determine the relationship between emotional intelligence and student achievement at SMP Negeri 1 Peterongan, Jombang Regency. The research design used was a correlation analytic method with a cross sectional approach, the measuring instrument used was a questionnaire with total sampling technique and the number of samples was 30 respondents Class VIII E students of SMP Negeri 1 Peterongan, Jombang Regency. The results of this study note that most students have moderate emotional intelligence with moderate learning achievement spearman rank statistical test results. obtained a significant number and probability (0.000) or a significant standard (0.05) or (p<a) then the coefficient value of 0.599 indicates that the relationship is quite strong, then H1 is accepted meaning there is a relationship of emotional intelligence to student achievement. Emotional Intelligence on Student Achievement Many studies have been conducted on brain dominance, basically showing that each hemisphere of the left and right brain has a different function so that moderate emotional intelligence and moderate learning achievement allow individuals to feel, understand correctly, then be able to use emotional power and sensitivity as information energy and influence learning achievement.